Comparison of Hanging Panels and Boundary Diffusers in a Reverberation Chamber. Issue 2 (June 2014) - Bradley, David T.; Müller-Trapet, Markus; Adelgren, Jacob; Vorländer, Michael
Achieving a diffuse sound field in a reverberation chamber is crucial for measurements of acoustic quantities such as sound absorption coefficient, scattering coefficient, and sound power level. Toward this aim, diffusing elements such as hanging panels or rotating diffusers are typically installed in the chamber. However, previous research has suggested that hanging panels violate certain theoretical assumptions regarding diffusivity. Also, rotating diffusers cause the chamber to be a time-variant system, precluding the use of some measurement approaches such as sine-sweep integrated impulse response techniques. Boundary diffusers are offered as an alternative in the current study. The effects of both hanging panels and boundary diffusers on sound field diffusivity in a scale reverberation chamber are systematically and comparatively analyzed. The field diffusivity is characterized based on the guidelines set forth in American and international standards, including ISO 354, ASTM C423, and ASTM E90. Resulting data suggests that these standardized methods do not adequately or rigorously quantify diffusivity. The relative effectiveness of hanging diffusers vs. boundary diffusers will be discussed.